Immunization of African Indigenous Pigs with Attenuated Genotype I African Swine Fever Virus OURT88/3 Induces Protection Against Challenge with Virulent Strains of Genotype I. Issue 5 (18th February 2015) - Mulumba‐Mfumu, L. K.; Goatley, L. C.; Saegerman, C.; Takamatsu, H.‐H.; Dixon, L. K.
Summary: The attenuated African swine fever virus genotype I strain OURT88/3 has previously been shown to induce protection of European breeds of domestic pigs against challenge with virulent isolates. To determine whether protective immune responses could also be induced in indigenous breeds of pigs from the Kinshassa region in Democratic Republic of Congo, we immunized a group of eight pigs with OURT88/3 strain and challenged the pigs 3 weeks later with virulent genotype I strain OURT88/1. Four of the pigs were protected against challenge. Three of the eight pigs died from African swine fever virus and a fourth from an unknown cause. The remaining four pigs all survived challenge with a recent virulent genotype I strain from the Democratic Republic of Congo, DRC 085/10. Control groups of non‐immune pigs challenged with OURT88/1 or DRC 085/10 developed signs of acute ASFV as expected and had high levels of virus genome in blood.